Does Cholinergic Stimulation Affect the P2X7 Receptor-Mediated Dye Uptake in Mast Cells and Macrophages? - Nurkhametova, Dilyara; Siniavin, Andrei; Streltsova, Maria; Kudryavtsev, Denis; Kudryavtsev, Igor; Giniatullina, Raisa; Tsetlin, Victor; Malm, Tarja; Giniatullin, Rashid (Frontiers in Cellular Neuroscience, 2020)
Background: Extracellular ATP is the powerful trigger of neuroinflammation mainly via activation of pro-inflammatory P2X7 receptors. Acetylcholine and nicotinic agonists can inhibit ATP-triggered release of the pro-inflammatory cytokines from immune cells via so-called ‘Cholinergic Anti-Inflammatory Pathway’. However, it remains unclear at what stage of ATP-induced signaling cholinergic agents provide this anti-inflammatory effect. Using the specific property of P2X7 receptor to open a pathway permeable to large molecules, associated with activation of inflammasome, we studied the action of cholinergic agents on the initial steps of P2X7 receptor activation. Methods: Freshly isolated mouse peritoneal mast cells, used as model of immune cells, were treated with ATP alone or in the presence of acetylcholine and nicotine. To assess P2X7 channels opening, mast cells permeability to the fluorescent dye YO-PRO1 was measured by the flow cytometry approach. Results: ATP efficiently opened P2X7 ion channels in mast cells, shown by the large uptake of YO-PRO1. This stimulatory effect was inhibited by the specific P2X7 antagonist A839977 confirming that YO-PRO1 uptake was mediated via ATP-gated P2X7 ion channels. Interestingly, cholinergic agents also slightly enhanced permeability of mast cells to YO-PRO1. However, both acetylcholine and nicotine failed to inhibit the stimulatory effect of ATP on P2X7 receptors. Conclusion. These data suggest that cholinergic agents do not act on the initial steps of P2X7 receptor activation, but likely mediate the anti-inflammatory effect downstream of ATP-driven signaling, probably at the stage of processing or release of the pro-inflammatory cytokines.